Adverse prognostic significance of CD20 expression in adults with Philadelphia chromosome-negative B-cell precursor acute lymphoblastic leukemia - Sébastien Maury; Françoise Huguet; Thibaut Leguay; Francis Lacombe; Marc Maynadié; Sandrine Girard; Adrienne de Labarthe; Emilienne Kuhlein; Emmanuel Raffoux; Xavier Thomas; Patrice Chevallier; Agnès Buzyn; et al. (Haematologica, 2010)
The prognostic significance of CD20 expression in B-cell precursor acute lymphoblastic leukemia (BCP-ALL) has been mostly studied in children and yielded conflicting results. In 143 adults with Philadelphia chromosome-negative BCP-ALL treated in the multicentric GRAALL 2003 trial, CD20 positivity over 20% was observed in 32% of patients. While not influencing complete remission achievement, CD20 expression was associated with a higher cumulative incidence of relapse (CIR) at 42 months (P=0.04), independently of the ALL high-risk subset (P=0.025). Notably, the negative impact of CD20 expression on CIR was only observed in patients with a white blood cell count (WBC) over 30×109/L (P=0.006), while not in those with a lower WBC. In the former subgroup, this impact translated into lower event-free survival (15% vs. 59% at 42 months, P=0.003). CD20 expression thus appears to be associated with a worse outcome, which reinforces the interest of evaluating rituximab combined to chemotherapy in CD20-positive adult BCP-ALL. ClinicalTrials.gov ID, NCT00222027.